EKSPLORASI KONSEP GEOMETRI PADA MEDALION GEOMETRIS CANDI KIDAL - Romadhon, Muhammad Syahru; Rosadi, Moch Roma Isa (UIN Imam Bonjol Padang, 2024)
This study aimed to investigate the geometric patterns of medallions in Kidal Temple using a qualitative approach with an ethnographic research design. The data was collected through interviews, observation, and documentation. The research utilized both the main instrument (the researcher themselves) and auxiliary instruments including interview guidelines, observation sheets, math concept suitability sheets, and documentation tools. The geometric concept of the medallions in Kidal Temple encompassed the circle, quadrilateral, and congruence on the circle. The outer side of the medallion was a flat circular shape, which was verified through measurement and instrument adjustment. On the inside of the geometric medallion, there was a rectangular flat shape formed by four lines. Another significant finding of this study was the concept of circle equality, as the center of the medallion exhibited the same characteristics as the outer part despite differing in size. It is important to note that the scope of this research is limited to ethnomathematics studies, specifically focusing on the relief form of geometric medallions. Consequently, further research is needed to explore the implications as like as learning Realistic Mathematic Education of these findings in the context of geometric medallions.